Twelve-Year Changes in Pre-Schoolers' Oral Health and Parental Involvement in Children's Dental Care: Results from Two Repeated Cross-Sectional Surveys in Lithuania - Apolinaras Zaborskis; Jaunė Razmienė; Augustė Razmaitė; Vilija Andruškevičienė; Julija Narbutaitė; Eglė Aida Bendoraitienė; Aistė Kavaliauskienė (MDPI AG, 2024)
Background and objectives: The role of parents and the family in promoting children's oral health is increasingly acknowledged in the dental literature. This study aimed to investigate twelve-year changes in pre-schoolers' oral health and parental involvement in children's dental care using data from two repeated cross-sectional surveys. The objectives were (1) to assess the temporal changes in children's dental health status and oral health-related behaviours, (2) to examine temporal changes in parental attitudes toward their children's oral health care, and (3) to analyze the associations between observed changes. Materials and methods: Two identical cross-sectional surveys were conducted in 2010/2011 (n = 294) and 2023 (n = 304). In both surveys, parents answered questions regarding their children's oral health care and completed the 38-item 'Parental Attitudes toward Children's Oral Health' (PACOH) scale, while the dental health of their 3-7-year-old children was clinically assessed. Changes in the examined characteristics were analyzed using general linear models. Results: Significant positive changes (p < 0.001) were observed when comparing the surveys: the dmf-t (decayed, missing, filled teeth) score for deciduous teeth decreased from 5.56 to 3.31; the Silness-Löe Plaque Index decreased from 1.45 to 1.15; the percentage of children brushing their teeth regularly increased from 33.0% to 55.3%; the percentage of parents assisting their child with tooth brushing increased from 19.2% to 85.1%; and regular visits to a children's dentist increased from 36.4% to 85.1%. Moreover, the study revealed better parental attitudes toward their children's oral health care, as reflected by a change in the total score of the PACOH scale from 112 to 122. Conclusions: It was concluded that changes in parental attitudes played a crucial role in driving positive trends in oral health-related behaviours, which likely contributed to the improvement of dental health in children. Therefore, understanding and influencing parental attitudes can be essential for promoting good oral health skills and good oral health in young children.